Evidence of regional sea-level rise acceleration for the North Sea - Steffelbauer, David B; Riva, Riccardo E M; Timmermans, Jos S; Kwakkel, Jan H; Bakker, Mark (Environmental research letters, 2022)
Global mean sea-level rise (SLR) has accelerated since 1900 from less than 2 mm yr −1 during most of the century to more than 3 mm yr −1 since 1993. Decision-makers in coastal countries, however, require information on SLR at the regional scale, where detection of an acceleration in SLR is difficult, because the long-term sea-level signal is obscured by large inter-annual variations with multi-year trends that are easily one order of magnitude larger than global mean values. Here, we developed a time series approach to determine whether regional SLR is accelerating based on tide gauge data. We applied the approach to eight 100-year records in the southern North Sea and detected, for the first time, a common breakpoint in the early 1990s. The mean SLR rate at the eight stations increases from 1.7 ± 0.3 mm yr −1 before the breakpoint to 2.7 ± 0.4 mm yr −1 after the breakpoint (95% confidence interval), which is unprecedented in the regional instrumental record. These findings are robust provided that the record starts before 1970 and ends after 2015. Our method may be applied to any coastal region with tidal records spanning at least 40 years, which means that vulnerable coastal communities still have time to accumulate the required time series as a basis for adaptation decisions in the second half of this century.